New Perspectives in Fluid Dynamics - Liu, Chaoqun (IntechOpen, 2015)
This book contains five chapters detailing significant advances in and applications of new turbulence theory and fluid dynamics modeling with a focus on wave propagation from arbitrary depths to shallow waters, computational modeling for predicting optical distortions through hypersonic flow fields, wind strokes over highway bridges, optimal crop production in a greenhouse, and technological appliance and performance concerns in wheelchair racing. We hope this book to be a useful resource to scientists and engineers who are interested in the fundamentals and applications of fluid dynamics.